2015
DOI: 10.1007/s10803-015-2451-4
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparison Between Pivotal Response Treatment (PRT) and Adult-Driven Applied Behavior Analysis (ABA) Intervention on Disruptive Behaviors in Public School Children with Autism

Abstract: Children with autism often demonstrate disruptive behaviors during demanding teaching tasks. Language intervention can be particularly difficult as it involves social and communicative areas, which are challenging for this population. The purpose of this study was to compare two intervention conditions, a naturalistic approach, Pivotal Response Treatment (PRT) with a structured ABA approach on disruptive behavior during language intervention in the public schools. A Randomized Clinical Trial (RCT) design was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 40 publications
(38 reference statements)
2
42
1
2
Order By: Relevance
“…Pivotal Response Treatment (PRT) is a behavioral intervention that has been effective in improving communication skills, increasing social interactions, and reducing the behavioral problems of children with autism [ 11 , 12 , 13 , 14 ]. This approach targets pivotal behaviors such as motivation, initiation, response to multiple symptoms, management and empathy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pivotal Response Treatment (PRT) is a behavioral intervention that has been effective in improving communication skills, increasing social interactions, and reducing the behavioral problems of children with autism [ 11 , 12 , 13 , 14 ]. This approach targets pivotal behaviors such as motivation, initiation, response to multiple symptoms, management and empathy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that PRT is more effective than the adult-directed applied behavior analysis (ABA) intervention [ 12 ]. The use of favored stimulus items and activities, rather than artificial stimuli and the presentation of the teaching within the context of natural interactions during the PRT sessions may have created more interest in the teaching sessions, thereby resulting in lower levels of disruptive behavior [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies using PRT have focused on improvement in social communication or cognitive ability. For example, several recent RCTs of PRT have shown significant improvement in language and social functioning (Hardan et al, 2014; Mohammadzaheri, Koegel, Rezaee, & Rafiee, 2014; Mohammadzaheri, Koegel, Rezaei, & Bakhshi, 2015). To date, though, no studies have investigated the effects of PRT on RRB reduction.…”
mentioning
confidence: 99%
“…The main focus of pivotal therapy is to adjust how parents and children respond to the multiple environmental cues that are part of their everyday lives. Pivotal therapy is practiced when the child is in his or her natural environment rather than a clinical setting offering an advantage over traditional approaches by enhancing motivation [114]. Another frequently used treatment is verbal behavior therapy.…”
Section: Behavioral Treatment Approachesmentioning
confidence: 99%